Appropriate school starting age: A focus on the cognitive and social development of a child (Journal of Education and Educational Development, 2020)
The early years are the most important in the emotional, social, physical and cognitive development of a child.. A child’s early experiences have an immense impact on the development of his/ her physical, emotional and cognitive skills. Therefore, it is very important to understand the kind of environment children need in the early years for their healthy development and also to understand when it is appropriate to begin their schooling in order to optimize their social, cognitive and emotional well-being. It is observed that the number of formal pre-schools have increased drastically in the past few years. Children between the ages of one to five are attending these pre-schools. This paper attempts to look into the various researches conducted to find out how early childhood experiences affect children; how their emotional and cognitive development occurs; and most importantly, whether or not starting school at an age earlier than seven years, benefits their academic achievement in the long run. The findings of the various researches indicate that children in the early years need to spend time in free play rather than in structured and scheduled school environments. This will also help them in their future academic success. Thus, starting school earlier than seven years of age is not beneficial socially or academically in the long run.